Modulatory effect of levodopa on the basal ganglia-cerebellum connectivity in Parkinson’s disease - Juyoung Jenna Yun; Subati Abulikemu; Kodchakorn Love Jangwanich; Yen F. Tai; Shlomi Haar (npj Parkinson's Disease)
Abstract Long-term levodopa use in Parkinson’s disease is associated with declining efficacy and motor complications. Understanding its effects on brain reorganisation is vital for optimizing therapy. Using data from Parkinson’s Progression Marker Initiative, we investigated levodopa’s impact on resting-state functional connectivity within the cortico-basal ganglia-cerebellum system in 29 patients, under drug-naïve and levodopa-medicated conditions. Univariate comparisons of inter-regional connectivity between conditions were conducted, and multivariate combinations of connections within and between networks were assessed. No significant effect of levodopa was found using the univariate seed-based approach. However, the network connectivity pattern between basal ganglia and cerebellum showed robust classification power. Eigenvector Centrality Mapping (ECM) further identified functional hubs, with cerebellar hubs being the only ones within the cortico-basal ganglia-cerebellum system affected by medication. Our study provides further insight into the importance of inter-network functional connectivity in Parkinson’s and the impact of levodopa medication, highlighting the often-overlooked role of the cerebellum.